Efficacy and Safety of Ropivacaine Addition to Intrathecal Morphine for Pain Management in Intractable Cancer - Ying Huang; Xihan Li; Tong Zhu; Jian Lin; Gaojian Tao (Hindawi Limited, 2015)
Objective. Although intrathecal drug infusion has been commonly adopted for terminal cancer pain relief, its adverse effects have made many clinicians reluctant to employ it for intractable cancer pain. The objective of this study is to compare the efficacy and security of an intrathecal continuous infusion of morphine and ropivacaine versus intrathecal morphine alone for cancer pain. Methods. Thirty-six cancer patients received either a continuous morphine (n=19) or morphine and ropivacaine (n=17) infusion using an intrathecal catheter through a subcutaneous port. Numerical Rating Scale (NRS) scores and the Barthel Index were analyzed. Adverse effects and complications on postoperative days 1, 3, 7, and 15 were also analyzed. Results. All patients experienced pain relief. Compared to those who received morphine alone, patients receiving morphine and ropivacaine had significantly lower postoperative morphine requirements and higher Barthel Index scores on the 15th postsurgical day (P<0.05). Patients receiving morphine and ropivacaine had lower NRS scores than patients receiving morphine alone on postoperative days 1, 3, 7, and 15 (P<0.05). Negative postsurgical effects were similar in both groups. Conclusions. Morphine and ropivacaine administration through intrathecal access ports is efficacious and safe and significantly improves quality of life.